Efikasi Ekstrak Bunga Kecombrang (Etlingera elatior) Terhadap Hama Crocidolomia pavonana di Laboratorium - Siti Shofiya Nasution; Muhammad Sayuthi; Julia Amanda (Universitas Batanghari, 2026)
Crocidolomia pavonana is an important pest of cruciferous crops that can cause severe damage and significantly reduce yield quality. Pest management in agricultural fields is still largely dependent on synthetic insecticides, which pose potential risks to the environment and human health. Consequently, the development of safer and more sustainable control strategies is required, including the use of plant-based insecticides. This study aimed to assess the efficacy of torch ginger (Etlingera elatior) flower extract as a botanical insecticide against C. pavonana larvae under in vitro laboratory conditions. The experiment was arranged in a completely randomized design with five extract concentrations, namely 0% (control), 2%, 4%, 6%, and 8%. Parameters observed included antifeedant activity, larval mortality, pupation rate, and adult emergence. The results demonstrated that the application of torch ginger flower extract had a highly significant effect on all observed parameters. Antifeedant activity and larval mortality increased with increasing extract concentration, with the highest mortality reaching 100% at the 8% concentration. In addition, the extract markedly suppressed pupal formation and adult emergence compared with the control. These insecticidal effects are presumably associated with secondary metabolites such as flavonoids, tannins, and saponins, which interfere with insect physiological processes and metabolism. Therefore, torch ginger flower extract shows strong potential as an effective and environmentally friendly botanical insecticide for controlling C. pavonana on cruciferous crops.